2022
DOI: 10.1186/s12915-021-01221-y
|View full text |Cite
|
Sign up to set email alerts
|

Modular evolution of secretion systems and virulence plasmids in a bacterial species complex

Abstract: Background Many named species as defined in current bacterial taxonomy correspond to species complexes. Uncertainties regarding the organization of their genetic diversity challenge research efforts. We utilized the Agrobacterium tumefaciens species complex (a.k.a. Agrobacterium biovar 1), a taxon known for its phytopathogenicity and applications in transformation, as a study system and devised strategies for investigating genome diversity and evolution of species complexes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 112 publications
1
23
0
Order By: Relevance
“…To date, the T6SS has been identified in several genera of seven phyla of Gram-negative bacteria, Acidobacteria , Bacteroidetes , Deferribacteres, Gemmatimonadetes , Nitrospirae , Planctomycetes, and Proteobacteria , being abundant in the latter 1 , 7 , 14 16 . Although widely present and diverse in these bacterial phyla, the T6SS has a patchy distribution, not being ubiquitous in all these bacterial genomes 8 , 14 , 17 , 18 . This suggests an association of the T6SS with horizontal gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the T6SS has been identified in several genera of seven phyla of Gram-negative bacteria, Acidobacteria , Bacteroidetes , Deferribacteres, Gemmatimonadetes , Nitrospirae , Planctomycetes, and Proteobacteria , being abundant in the latter 1 , 7 , 14 16 . Although widely present and diverse in these bacterial phyla, the T6SS has a patchy distribution, not being ubiquitous in all these bacterial genomes 8 , 14 , 17 , 18 . This suggests an association of the T6SS with horizontal gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“… 2021 , Chou et al . 2022 ). Among plants, non-core genes of Arabidopsis thaliana , rice, rapeseed, cabbage, sunflower, and wheat are known actuators of the host–pathogen warfare (Zhao et al .…”
Section: Research Outlooks and Conclusionmentioning
confidence: 99%
“…A T6SS-encoding locus is highly conserved in the genome of plant pathogenic bacterium Agrobacterium tumefaciens and the apparatus functions as an antibacterial weapon [23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…A T6SS-encoding locus is highly conserved in the genome of plant pathogenic bacterium Agrobacterium tumefaciens and the apparatus functions as an antibacterial weapon (Chou et al, 2022;Ma et al, 2014;Wu et al, 2021;Yu et al, 2020). We previously revealed that A. tumefaciens strain C58 deploys two Type VI DNase effectors (Tde1 and Tde2) as the major antibacterial weapons, in which the cognate immunity proteins (namely Tdi1 and Tdi2) prevent autointoxication (Ma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%